PENGEMBANGAN LKS MATERI OPTIK DENGAN PENDEKATAN SAINS TEKNOLOGI MASYARAKAT BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Zahidah, Nila; Ellianawati, Ellianawati; Darsono, Teguh (UPEJ Unnes Physics Education Journal, 2020)
This research aims to design the student worksheet based on STS that can help students improving their critical thinking skills. This research are using R&D (Research and Development) method. The research is pre-experimental design with one group pretest-posttest design. The results show the advisability of student worksheet based on STS have average score from four aspect of a feasible is 93.61% with the criteria is very feasible. The improvement student?s critical thinking skills after using student worksheet based on STS tested by N-Gain test get the result of 0.48 with medium criteria. The students give good response with the average score is 77.69%, due to the feasible of students? worksheet is very feasible. Based on to the result, it can concluded that the students? worksheet based STS optical matter for grade VIII junior high school students very feasible and effective enough for used in the learning activities.